PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI DI LINGKUNGAN BADAN PENGELOLA DAN KEUANGAN ASET DAERAH (BPKAD) KOTA TASIKMALAYA - Aprianty, Diana (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 6 No 2 (2021): Jurnal Kajian Ekonomi dan Kebijakan Publik, 2021)
This study entitled "The Effect of Communication on Employee Performance in the Regional Financial and Asset Management Agency (BPKAD) Kota Tasikmalaya". The main problem is: Communication is not well established and the work intensity is quite high. For the framework of thought takes Kamrin's theory of communication, where the dimensions are upward communication, downward communication and horizontal communication. Meanwhile, employee performance takes the theory from Mangkunegara, where the dimensions are work quality, work quantity, employee consistency, cooperation and employee attitudes. The research method used is an associative research method with a quantitative approach. The results of the communication calculation test have a positive effect on employee performance. The coefficient of determination (R2) is 0.983 which shows 98.3% of employee performance variables are positively influenced by communication variables, while the remaining 1.7% is explained by other variables.